The Dynamic of Muzakki’s Perception and Its Effect on Zakat Collection in Badan Amil Zakat Nasional Pekanbaru - Maghfirah Maghfirah (Jurnal Ilmiah Ekonomi Islam, 2021)
Management of Zakat has great potential to optimize the potential of Islamic philanthropy based on Law no. 23 of 2011. But in reality, there are still many people who do not understand the content in the Act. Therefore, this study aims to analyze Muzakkī’s perception of the obligation to pay zakat through Baznas as written in Law No.23 of 2011 and its effect on the collection of zakat funds in Pekanbaru Baznas. This study uses an empirical or sociological juridical approach and is analytically descriptive. The method of collecting data through interviews and questionnaires with qualitative data analysis methods is juridical. The results of the study are that there are still many Muzakkī who do not know the obligation to pay zakat in Baznas, Muzakkī’s weak trust in Baznas, and Baznas are considered to have not succeeded in empowering Mustaḥiq's economy. So that Muzakkī’s perception of the obligation to pay zakat and understanding Law No.23 of 2011 has a negative effect on the collection of zakat funds in Badan Amil Zakat Nasional Pekanbaru